2003
DOI: 10.1097/00003072-200301000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Tc-99m MIBI Uptake and Its Relation to the Proliferative Potential of Brain Tumors

Abstract: High-grade brain tumors have increased Tc-99m MIBI uptake compared with that of low-grade tumors. Tc-99m MIBI uptake is correlated with the percentage of the S-phase fraction of the cell and the aneuploidy level of the brain tumor. This preliminary report suggests that Tc-99m MIBI imaging may be useful in the evaluation of the biologic characteristics of brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…No study has examined the uptake mechanism of Tc-99m MIBI in parathyroid carcinoma. Related studies suggest that intense uptake and delayed retention may be caused by high mitochondrial content, increased perfusion, or increased metabolic activity [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…No study has examined the uptake mechanism of Tc-99m MIBI in parathyroid carcinoma. Related studies suggest that intense uptake and delayed retention may be caused by high mitochondrial content, increased perfusion, or increased metabolic activity [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, higher tracer uptake by glioma on SPECT was shown to be associated with higher grade and decreased response to chemotherapy of gliomas (11)(12)(13)(14). In addition, higher technetium-99m-methoxyisobutylisonitrile ( 99m Tc-MIBI) uptake was demonstrated to correlate with higher proliferative potential of gliomas and with worse survival (15)(16)(17)(18)(19). However, to the best of our knowledge, previous studies employed SPECT scans only once during the treatment period and currently there are no studies evaluating the association of repeated SPECT scans during perioperative periods with the prognosis of malignant glioma patients.…”
Section: Introductionmentioning
confidence: 95%
“…Baillet and Ak have studies on 99mTc-sestamibi. They proved the relation of increased tracer uptake in high aneauploidi of DNA in tumor and so high degree of malignancy (1,3). Another study showed 99mTc-sestamibi SPECT has 73% sensitivity and 85% specifity (11).…”
Section: Discussionmentioning
confidence: 97%